Providing feedback on remote classes - analysis of selected applications - Kruszyńska, Agnieszka (Activation-innovation-inspiration in (glotto) didactics, 2022)
During the SARS-CoV-2 pandemic outbreak at the turn of 2019/2020, distance learning has become a compulsion, but also a solution that allows to maintain the continuity of education all over the world. The purpose of this article is to provide an analysis of educational applications designed to create interactive materials and their feedback. The tools were selected from an online survey of 278 teachers participating in the online learning webinar, and then analyzed by 6 criteria: 1) The ability to track students' progress; 2) Possibility to personalize the feedback; 3) Possibility of individualization of feedback; 4) Providing automatic and immediate feedback, 5) Possibility of direct contact between the student and the teacher, 6) Possibility of verifying open tasks. The results presented can help teachers, especially foreign language teachers, choose the tools that best suit their needs, and most importantly, suit the needs of students.